Memahami dan Mengatasi Kecemasan dalam Pembelajaran Matematika - Kusmartiningrum, Shinta Agistya; Prayitno, Anton; Baidawi, Muhammad (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
Anxiety in learning mathematics is a significant issue that affects students' ability to understand and solve mathematical problems. Factors such as the learning environment, social stereotypes, and personal factors play a crucial role in triggering this anxiety. Research has highlighted the negative consequences of math anxiety on students' performance in everyday problem-solving and their academic achievement. Various strategies have been proposed to address math anxiety, including cognitive-behavioral therapy, cooperative learning, and realistic mathematics approaches. The implementation of innovative strategies such as gamification, flipped classrooms, and the integration of the history of mathematics has also proven successful in increasing students' interest and understanding of mathematics. Evaluations of studies indicate that cooperative learning models and guidance services focused on problem-solving have been effective in improving mathematics learning outcomes. With a deep understanding of the factors influencing math anxiety and efforts to address them, it is hoped that the quality of mathematics learning can be improved and students' anxiety in learning the subject can be reduced.